OCEANS 2015 - MTS/IEEE Washington 2015
DOI: 10.23919/oceans.2015.7401876
|View full text |Cite
|
Sign up to set email alerts
|

Discriminative sparsity for Sonar ATR

Abstract: Advancements in Sonar image capture have enabled researchers to apply sophisticated object identification algorithms in order to locate targets of interest in images such as mines [1] [2]. Despite progress in this field, modern sonar automatic target recognition (ATR) approaches lack robustness to the amount of noise one would expect in real-world scenarios, the capability to handle blurring incurred from the physics of image capture, and the ability to excel with relatively few training samples. We address th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 13 publications
1
14
0
Order By: Relevance
“…Next, we present how well SRC with LPM performs when compared to a popular image classification technique, SIFT feature SVM. In [11] and [2] the authors implemented SIFT feature SVMs towards Sonar ATR, the former of which in to handle pose-diversity. For this reason, we used this algorithm on our test images to provide context for SRC with LPM.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Next, we present how well SRC with LPM performs when compared to a popular image classification technique, SIFT feature SVM. In [11] and [2] the authors implemented SIFT feature SVMs towards Sonar ATR, the former of which in to handle pose-diversity. For this reason, we used this algorithm on our test images to provide context for SRC with LPM.…”
Section: Methodsmentioning
confidence: 99%
“…We found a L1LS method to produce the most satisfactory results for our work. [2] showed that it is possible produce compelling classification rates on consistently-posed test images of Sonar image using SRC. That said, in real-world cases the ability to collect targets all arranged in geometrically ideal positions is difficult if not infeasible.…”
Section: Srcmentioning
confidence: 99%
See 3 more Smart Citations